2012
DOI: 10.6018/analesps.28.2.148931
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison and related psychosocial variables: a review of cancer and chronic pain

Abstract: Resumen: El concepto de comparación social ha despertado gran interés en a investigación que lo evalúan con el estado de salud. El presente trabajo tiene como objetivo revisar el constructo de comparación social en enfermos oncológicos y de dolor crónico y estudiar la relación de la comparación social con otras variables psicosociales y resultados adaptativos. Para ello se consultaron las bases de datos Medline y PsycInfo y se obtuvieron un total de 69 trabajos para enfermos oncológicos y 22 para pacientes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
3
4
0
2
Order By: Relevance
“…The other group, or more "adaptive" profile, included women who showed moderate levels of pain perception, with a lower level of anxiety and depression and more frequent "favorable" social comparison strategies (upward identification and downward contrast). These profiles are consistent with other studies that have correlated these variables in the same way (Terol et al, 2012;Cabrera-Perona et al, 2017) or have identified similar groups of patients in FM (Giesecke et al, 2003;De Souza et al, 2009;Calandre et al, 2011;Keller et al, 2011;Docampo et al, 2013). Giesecke et al (2003) proposed three profiles, one of which shows moderate anxiety / depression and less pain, while another presents a higher level of anxiety / depression and pain.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The other group, or more "adaptive" profile, included women who showed moderate levels of pain perception, with a lower level of anxiety and depression and more frequent "favorable" social comparison strategies (upward identification and downward contrast). These profiles are consistent with other studies that have correlated these variables in the same way (Terol et al, 2012;Cabrera-Perona et al, 2017) or have identified similar groups of patients in FM (Giesecke et al, 2003;De Souza et al, 2009;Calandre et al, 2011;Keller et al, 2011;Docampo et al, 2013). Giesecke et al (2003) proposed three profiles, one of which shows moderate anxiety / depression and less pain, while another presents a higher level of anxiety / depression and pain.…”
Section: Discussionsupporting
confidence: 89%
“…They also compare themselves with others (referents) on "similar health problems" and on contents such as "symptoms." These results coincide with another recent study on FM (Terol et al, 2007b(Terol et al, , 2012 but differ from findings in other chronic patients (rheumatoid arthritis or cancer patients) who used upward identification and/or downward contrast more often (Blalock et al, 1990;De Vellis et al, 1990;Dibb and Yardley, 2006;Terol et al, 2007bTerol et al, , 2012. The findings regarding the profiles in FM patients revealed two different subgroups.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The Social Comparison Theory [1] proposes that a lack of information and uncertainty can trigger social comparison processes, and this is particularly common in the case of chronic illness [2][3][4][5][6]. Patients will try to search for relevant information and compare themselves with other patients with the same condition, such as the same illness diagnosis [3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%